Journal Club: An Innovative Teaching Practice to Foster Peer Connection and Enhance Information Literacy Skills - Hanneke Croxen; Jody Nelson; Lisa McKendrick-Calder (Teaching & Learning Inquiry: The ISSOTL Journal, 2023)
This project aimed to better understand the impact and student experience of an innovative teaching strategy focused on information literacy (IL) for first-year undergraduate nursing students. Information literacy (IL) involves the development of a set of abilities essential for higher education learners, such as the ability to identify, critically evaluate, understand, and apply scholarly literature (ACRL 2013), yet studies often demonstrate that these IL skills are lacking and need further development (Bury 2016; Saunders 2012). Traditional methods of addressing this need center around stand-alone librarian-led IL sessions, which cannot provide the time or space needed to develop critical reading and reflection practices. Within our context of nursing, this is a common challenge; one study found that 40% of second-year nursing students have difficulty reading journal articles (Chaudoir et al. 2016), despite IL being an essential skill for nursing practice (Mitchell and Pereira-Edwards 2022). In an attempt to address learner needs, a course instructor and librarian teamed up. Journal clubs, used in practice settings to maintain currency and promote EBP behavior (Wilson et al. 2015), have been used successfully in other health education contexts (Steenbeek et al. 2009; Szucs et al. 2017; Thompson 2006). This application is referred to as evidence-based practice (EBP) and is an essential component of nursing practice. Having activities for undergraduate nursing students that instill EBP aims to ensure that it will be incorporated into practice after graduation (Mitchell and Pereira-Edwards 2022). Instead of the traditional librarian-led IL sessions, a first-year nursing course was redesigned to utilize a guided journal club approach to enhance the ability to seek, read, and interpret journal literature. Journal club activities took place over eight weeks, alternating guided activities with brief IL lessons, and culminated in a group journal club assignment. Students were placed in small groups based on an area of practice they wanted to learn more about. Activities were scaffolded starting with introducing a research database and basic literature searching strategies. As students progressed through the term’s journal club activities, they were asked to find articles related aligned with course topics and their area of practice, critique and present their articles to their group members, and then apply their interpretations. A survey was used to measure the impact of journal club on student IL self-efficacy, as measured through the validated Information Literacy Self-Efficacy Scale (ILSES) developed by Kurbanoglu et al. (2006). Initial findings support journal club as an effective modality to enhance students’ self-efficacy in specific areas of IL. Additionally, other valuable outcomes of this strategy were discovered. For example, students reported becoming more comfortable collaborating with peers and anecdotal reports showed students developed friendships with peers. This scaffolded journal club approach to discipline-specific IL learning would translate well to other contexts, particularly those that require a significant grounding in reading and understanding disciplinary research. The journal club activities are available at: https://tinyurl.com/JournalClubPosterISSOTL2022, or by contacting the authors.